BIOLOGY AND FISHERY OF ’CHOO PARAI’, SELAROIDES LEPTOLEPIS (CUVIER AND VALENCIENNES) 1. Food and Feeding Habits - Tandon, K K (Indian Journal of Fisheries, 2015)
Carangids form a commercially important group of fishes in India but very little work has been done on their biology. The few available references to the subject being those of Chacko (1949), Mahadevan (1950), Datar (1954), KuthaUngam (1955 6), Chacko and Mathew (1956) and Vijayaraghavan (1957) on various species of horse-mackerel. The author, therefore, took up the study of Selaroides leptolepis (Cuv. & Val.), one of the common food Carangids of the Gulf of Mannar and the Palk Bay in the vicinity of Mandapam. The work was initiated in May 1957 and was carried out at the Central Marine Fisheries Research Station, Mandapam Camp. The present paper deals with the food of this fish